Studi Komparatif Pola Pertumbuhan Ikan Endemik Depik (Rasbora tawarensis Weber & de Beaufort, 1916) Menggunakan Linear Allometric Model (LAM) Berdasarkan Musim di Danau Laut Tawar, Aceh Tengah - Harahap, Syaiful Ramadhan; Sukendi, Sukendi; Siregar, Yusni Ikhwan; Nofrizal, Nofrizal; Hairussalam, Hairussalam; Syafriansyah, Syafriansyah; Yusapri, Andi; B, Arief Rachman; Ramses, Ramses (Program Studi Pendidikan Biologi, Universitas Riau Kepulauan, 2024)
This study aimed to compare the growth pattern of depik (Rasbora tawarensis Weber & de Beaufort, 1916) using a Linear Allometric Model (LAM) in different seasons in Lake Laut Tawar (LLT), Aceh Tengah. The results showed that seasonal differences affected the length-frequency size distribution, length-weight relationship, and condition factors but did not affect the growth pattern of depik in LLT. A comparison of growth patterns using LAM showed no significant differences, with a tendency for negative allometric patterns (b